The Consistencies of Y-Chromosomal and Autosomal Continental Ancestry Varying among Haplogroups - Chuan-Chao Wang; Lei Shang; Hui-Yuan Yeh; Lan-Hai Wei (Wolters Kluwer Medknow Publications, 2016)
The Y-chromosome has been widely used in ancestry inference based on its region-specific haplogroup distributions. However, there is always a debate on how informative such a single marker is for inferring an individual's genetic ancestry. Here, we compared genetic ancestry inferences at continental level made by Y-chromosomal haplogroups to those made by autosomal single-nucleotide polymorphisms in 1230 samples of Affymetrix Human Origins dataset. The highest ancestry proportions of a majority of individuals match the highest average continental-ancestry proportions in haplogroups A, B, D, H, I, K, L, T, O, and M. The high consistencies have not been observed in haplogroups E, C, G, J, N, Q, and R, but in some of their sublineages, such as E1a, E1b1a1, E1b1b1b1a, E2b1a, J1a2b, Q1a1a1, Q1a2a1a1, R1b1a2a1a, and R2. Although the consistencies of Y-chromosomal and autosomal continental ancestry vary among haplogroups, Y-chromosome could provide valuable clues for individual's continental ancestry.